Impact of Comorbidities and Antiplatelet Regimen on Platelet Reactivity Levels in Patients Undergoing Transcatheter Aortic Valve Implantation. Issue 3 (September 2021) - Trejo-Velasco, Blanca; Tello-Montoliu, Antonio; Cruz-González, Ignacio; Moreno, Raul; Baz-Alonso, Jose A.; Salvadores, Pablo J.; Romaguera, Rafael; Molina-Navarro, Eduardo; Paredes-Galán, Emilio; Fernández-Barbeira, Saleta; Ortiz-Saez, Alberto; Bastos-Fernandez, Guillermo; et al.
Abstract : Abstract: The aim of our study is to assess the impact of anemia, chronic kidney disease, and diabetes mellitus on platelet reactivity (PR) in patients with severe aortic stenosis, both at baseline and after transcatheter aortic valve implantation (TAVI). This study is a prespecified subanalysis of the REAC-TAVI prospective, multicenter trial that included patients pretreated with aspirin + clopidogrel before TAVI. PR was measured at baseline and at 5 different time points after TAVI with the VerifyNow assay (Accriva Diagnostics, San Diego, CA), over a 3-month follow-up period. Patients with high PR (HPR) at baseline, before TAVI (n = 48) were randomized to aspirin + clopidogrel or aspirin + ticagrelor for 3 months, whereas those with normal PR (NPR) (n = 20) were continued on aspirin + clopidogrel. A "raiser response" in PR was defined as an increase in PR units >20% of baseline after TAVI. Patients with HPR before TAVI presented concomitant anemia and chronic kidney disease more frequently than their counterparts with NPR. Anemia and higher body mass index were independently associated with HPR to clopidogrel at baseline. Moreover, anemic patients with baseline HPR who were continued on clopidogrel presented higher PR after TAVI than patients with HPR switched to ticagrelor. All patients with baseline NPR presented a "raiser response" after TAVI, which was nonexistent among patients with HPR managed with ticagrelor. In summary, anemia seems as a relevant factor associated with baseline HPR and higher PR after TAVI in patients with baseline HPR randomized to clopidogrel, whereas ticagrelor proved more effective than clopidogrel at attaining sustained reductions in PR during follow-up, regardless of baseline comorbidities. Abstract : Supplemental Digital Content is Available in the Text.